Sustainable Construction Supply Chain Management In Southeastern Nigeria: A Case For E-Commerce - Okoye, Oluchukwu Nwabufo N. (Transactions on Engineering and Computing Sciences, 2023)
Engineering and technology are two concepts that complement each other and are necessary ingredients for sustainability in a society either economic, social, etc. Growth in engineering and technology stimulates growth in other sectors of the society and one such sector is the telecommunication sector which gave rise to e-commerce technology. This e-commerce technology is very essential in our society, particularly in the construction industry. 105 respondents were sampled and administered questionnaires in the south-eastern states of Nigeria. The questionnaire contained perceived advantages of e-commerce and questions to ascertain if the respondents would accept the e-commerce technology and why and if they would use it to purchase especially construction materials identified from reviewed literature. With these, a relationship between willingness to purchase construction material using e-commerce and trust was established. Both descriptive and inferential statistics were used in analyzing the data. Results indicate that the e-commerce technology is welcome irrespective of some small bias and that convenience, provision of information, and reduction of fleecing of persons were some of the major reasons why they subscribed to the idea. Also, results show that purchasing construction materials through an e-commerce platform has huge potential. A significant positive relationship was found between willingness to purchase construction materials using e-commerce and trust in Nigeria. The study concludes by recommending important measures to be taken such as: Innovation and reforming of engineering education, enlightenment of the society on how to use e-commerce, upgrading research work and improvement of investment policies to create an attractive investment environment.